Uji Daya Hambat Anti Bakteri Air Perasan Daging Buah Nanas (Ananas Comosus (L) Merr Var. Queen) terhadap Bakteri Eschericia Coli - Pieter Julius Daely; Sarwendah Sarwendah; Heronimus C.G Laia; Suhartina Damardi (Universitas Batanghari Jambi, 2019)
Pineapple fruit (Ananas comosus (L) Merr) is one type of tropical fruit that is consumed by many people. Pineapple is also commonly used by the community as an antibacterial, anti-inflammatory, anti-coagulant, and anti-cancer. The purpose of this study was to determine the effectiveness of the antibacterial inhibitory effect of pineapple juice (Ananas comosus (L) Merr Var. Queen) on Eschericia coli bacteria. This study used an experimental laboratory method with disc diffusion and using ciprofloxacin disc as a positive control and distilled water as a negative control. Based on the results of research that has been done, it can be concluded that pineapple juice (Ananas comosus (L) Merr Var. Queen) at a concentration of 25%, 50%, 75%, and 100% has the effectiveness as an antibacterial in inhibiting the growth of Eschericia coli bacteria.